Self-tuning fuzzy logic control of quarter car and bridge interaction model - Mehmet Akif Koç; Mustafa Eroğlu; Recep Kozan; İsmail Esen (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this study, active suspension control of the interaction between the bridge can be modeled according to the Euler-Bernoulli beam theory, and the quarter car model with three degrees of freedom is studied. The active suspension system consists of a spring, damper, and linear actuator. The active suspension control is designed using classical PID and self-tuning fuzzy PID (STFPID) to reduce the vehicle body's disruptive effects. To determine the performance of the designed controllers, two different road profiles with the bridge oscillations caused by the bridge flexibility were considered as the disruptive effect of the vehicle. When the simulation results were examined in terms of passenger seat displacement and acceleration, the proposed STFPID method significantly increased road holding and ride comfort.